Induced selection of tebuconazole-resistant Aspergillus flavus isolates during germination of treated corn seeds - Chiara Morena; Cesare Accinelli; Veronica Bruno; Hamed K. Abbas; Ryan T. Paulk; W. Thomas Shier (Journal of Agriculture and Food Research)
Azole fungicides are used for spraying crops and also in seed treatments of corn, wheat and other important agricultural crops, in which seeds are dressed with a plastic-like coat containing an azole fungicide and other seed and seedling protection agents. In this study, the effect of tebuconazole in corn seed treatment on selecting for tebuconazole-resistant A. flavus isolates was investigated. Seed-borne A. flavus isolates growing during seed germination were tested for tebuconazole resistance. When seeds were treated with increasing dosages of tebuconazole, the relative abundance of resistant isolates increased. At the recommended dosage, up to 72.1 % of the seed borne A. flavus isolates that emerged from germinating seeds were resistant to tebuconazole. Resistance increased to 83.4 and 95.1 %, when dosages were doubled or quadrupled, respectively. Application of tebuconazole also increased the abundance of aflatoxin-producing isolates of A. flavus, from 32.2 % in untreated seeds to 67.4 % in seeds receiving the highest dosage. Results from this study suggest that seed treatment with tebuconazole should be included in the list of hotspots that induce resistance to azole antifungals and that measures and strategies, such as alternative fungicides with different metabolic targets, should be considered for reducing this risk.